English Language Acquisition of Indonesian Kindergarten Students in Tahsin for Kids Madania Foundation Australia - Losi Sabbilla; Miftachudin Miftachudin (Alsuna: Journal of Arabic and English Language, 2022)
Purpose - The objectives of this research are to find out the methods used by Indonesian students in acquiring their English proficiency and to recognize the challenges and strategies of Indonesian student in acquiring their English proficiency in foreign country. Design/methodology/approach - The research methodology used in this research was descriptive qualitative. The techniques of collecting data were interview, documentation, and audiovisual and digital materials to gather the data. The subjects of this research were kindergarten students in Tahsin for Kids Madania Foundation in Australia. Findings/results – The writer concluded that most of Indonesian students who live in foreign country used English as their second language. While the challenges of acquiring English are flip translation, teaching suitable and correct English, learning English from Indonesian parents, preparing the parents and children before enrolling kindergarten, and child speech delay. Originality/value - There are a lot of method used by indonesia students in acquiring English, it given by their closer environment such as family at home, teachers and friends at school. Paper type – Research paper